Scattering of 255 MeV Electrons at (220) Channeling in Silicon Crystal; RREPS-13. Radiation from Relativistic Electrons in Periodic Structures and Meghri-13. Electron, Positron, Neutron and X-ray Scattering under External Influences - Takabayashi Y. (2013, 2013)
Title screen.